THE RELATIONSHIP BETWEEN SAFETY CLIMATE WITH OCCUPATIONAL SAFETY AND HEALTH (OSH) IN EMPLOYEES OF THE MINE DEPARTMENT AND RAW MATERIAL MANAGEMENT OF PT. XYZ - Wahyuni, Indah; Amir, Arni; Rahayuningsih, Tri; Armalita, Rani; Pratama, Weno (Islamic Psychology Study Program, Institut Agama Islam Negeri Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
This study aims to see the relationship between safety climate and occupational safety and health (OSH) for employees of the Mining and Raw Materials Management Department of PT. XYZ. The research method used in this study is a quantitative method with Spearman's Rho analysis technique. Participants in this study consisted of 100 employees of the Mining and Raw Materials Management Department of PT. XYZ was obtained using the accidental sampling technique. Data collection was carried out using the 24-item Nordic Occupational Safety Climate Questionnaire (NOSACQ-24) and the Workplace Health and Safety Instrument German (WHASI-G). The reliability on the NOSACQ-24 measuring instrument is .905 and on the WHASI-G measuring instrument is .911. The results of this study indicate that there is a significant positive relationship between safety climate and occupational safety and health (OSH). This can be seen from the significance obtained by .000 (p<.05) and the correlation coefficient value of .699.